Rai Community and Shifting Cultivation Practices in Eastern Nepal: A Study of Balakhu, Okhaldhunga - Sapkota, Khila Nath (Patan Prospective Journal, 2023)
Shifting cultivation is a form of land use pattern among poor and indigenous communities with a rotation of cultivation and follow in the same unit of land. Thousands of indigenous people, with majority households for subsistence living, are depending on shifting cultivation practices. Shifting cultivation in Nepal, locally called as Khoriya or Bhasme, is a land use practice in which indigenous communities clear and cultivate secondary forests in plots of different sizes, leave these plots to regenerate naturally through fallows of medium to long duration. This practice is in transition these days with rising population of shifting cultivators and demand of more food stuff. This case study demonstrates the relationship among land use practices, people livelihood and health issues of Rai community who have involved in shifting cultivation practices in Balakhu Village of Okhaldhunga.